PENYULUHAN PEMBUATAN KOMPOS DARI LIMBAH RUMAH TANGGA DI DESA DELI TUA BARAT - Herviani Sari; Firdaus Fahdi; Bahtera Bin David Purba; Hengky Frengki Manulang (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
Garbage has become a classic problem that is constantly discussed and never finished in Indonesia. The dense population and settlements make the amount of waste produced is also increasing, because the waste is the result of daily human activities. With the increasing number of residents and dense settlements, the amount of waste will also continue to accumulate, therefore we as a group that cares about the environment and is tasked with providing useful and informative information to the community conduct counseling about the importance of processing household waste independently, one of which is the manufacture of fertilizers. compost with a simple composter. It is hoped that this activity can increase public awareness about wise steps to dispose of waste and adapt the concept of zero waste in everyday life. The location of this community service is in the village of West Deli Tua, Deli Tua District, Deli Serdang Regency. North Sumatra. The location of West Deli Tua was chosen as the research location considering the dense population and the density of population activities in the West Deli Tua village which has the potential to produce a lot of waste, especially household waste.